Distinct and conserved transcriptomic changes during nematode‐induced giant cell development in tomato compared with Arabidopsis: a functional role for gene repression. Issue 4 (4th February 2013) - Portillo, Mary; Cabrera, Javier; Lindsey, Keith; Topping, Jen; Andrés, Maria Fe; Emiliozzi, Mariana; Oliveros, Juan C.; García‐Casado, Gloria; Solano, Roberto; Koltai, Hinanit; Resnick, Nathalie; Fenoll, Carmen; et al.
Summary Root‐knot nematodes (RKNs) induce giant cells (GCs) from root vascular cells inside the galls. Accompanying molecular changes as a function of infection time and across different species, and their functional impact, are still poorly understood. Thus, the transcriptomes of tomato galls and laser capture microdissected (LCM) GCs over the course of parasitism were compared with those of Arabidopsis, and functional analysis of a repressed gene was performed. Microarray hybridization with RNA from galls and LCM GCs, infection–reproduction tests and quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) transcriptional profiles in susceptible and resistant (Mi‐1) lines were performed in tomato. Tomato GC‐induced genes include some possibly contributing to the epigenetic control of GC identity. GC‐repressed genes are conserved between tomato and Arabidopsis, notably those involved in lignin deposition. However, genes related to the regulation of gene expression diverge, suggesting that diverse transcriptional regulators mediate common responses leading to GC formation in different plant species. TPX1, a cell wall peroxidase specifically involved in lignification, was strongly repressed in GCs/galls, but induced in a nearly isogenic Mi‐1 resistant line on nematode infection. TPX1 overexpression in susceptible plants hindered nematode reproduction and GC expansion. Time‐course and cross‐species comparisons of gall and GC transcriptomes provide novel insights pointing to the relevance of gene repression during RKN establishment.